PENINGKATAN PEMAHAMAN MATEMATIKA SISWA SEKOLAH DASAR MELALUI PENGEMBANGAN MEDIA PEMBELAJARAN MAJAMAT PADA MATERI KELILING BANGUN DATAR - Fitriya, Ananda; Kurnia, Ira Restu (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Improving the mathematical ability of elementary school students is important to do as a provision for students in solving problems in everyday life. But in it’s application, it is not uncommon for students to feel less enthusiastic in following learning. By conducting learning using developed learning media, students will feel more enthusiastic in following the learning delivered. The research was conducted on grade III students in the even semester of the 2022/2023 academic year at SD Islam Plus An-Nur This research uses a development research method with the ADDIE model. The learning media developed is Majamat (mathematics magazine). Majamat (mathematics magazine) is a learning magazine that contains material about the circumference of flat wakes. In it’s development, Majamat (mathematics magazine) received an assessment from validators, namely 90.77% from subject content experts, 98.67% from learning media design experts, and 84.62% from linguists. In addition, Majamat (mathematics magazine) obtained the results of educator responses of 75% and student responses of 95.88%. Majamat (mathematics magazine) also obtained an effectiveness score of 80.53 in improving students' mathematical abilities. So it can be concluded that using Majamat (mathematics magazine) can help improve the mathematical ability of students.